The Effect of Principal’s Academic Supervision and Work Discipline on Teacher’s Performance - Gandi, Gandi; Fitria, Happy; Eddy, Syaiful (Yayasan Sembilan Pemuda Indonesia, 2024)
This study aims to determine the Effect of Principal Academic Supervision and Work Discipline on Teacher Performance at SD Negeri Gugus Satu Sungaiselan. This type of research is quantitative research with a research design using an ex post facto research design. The sample in this study was a total of all teachers at SD Negeri Gugus Satu Sungaiselan consisting of 81 teachers. data collection technique using a questionnaire. Data analysis techniques using quantitative descriptive analysis techniques, and multiple regression. The results of this study state that 1) there is a significant effect of the principal’s academic supervision on the performance of teachers at SD Negeri Gugus Satu Sungaiselan; 2) there is a significant effect of work discipline on teacher performance at SD Negeri Gugus Satu Sungaiselan 3) there is a significant effect jointly with the academic supervision of the school principal and work discipline on the performance of SD Negeri Gugus Satu Sungaiselan teachers.